Reasons for canakinumab initiation among patients with periodic fever syndromes: a retrospective medical chart review from the United States - Peter Hur; Kathleen G. Lomax; Raluca Ionescu-Ittu; Ameur M. Manceur; Jipan Xie; Jordan Cammarota; Raju Gautam; Navneet Sanghera; Nina Kim; Alexei A. Grom (BMC, 2021)
Abstract Background Although canakinumab has demonstrated efficacy in multiple trials in patients with periodic fever syndromes (PFS), the evidence on initiation of canakinumab among PFS patients in real world setting is not well understood. We aimed to characterize the reasons for canakinumab initiation among patients with PFS, specifically, cryopyrin-associated periodic syndrome (CAPS), hyperimmunoglobulin D syndrome/mevalonate kinase deficiency (HIDS/MKD), TNF receptor-associated periodic syndrome (TRAPS) and familial Mediterranean fever (FMF). Methods Physicians retrospectively reviewed the medical charts of PFS patients prescribed canakinumab between 2016 and 2018. Information collected included patient clinical characteristics, reasons for previous treatment discontinuation and canakinumab initiation. The results were summarized for overall patients, and by children (< 18 years) and adults and by subtype of PFS. Results Fifty-eight physicians in the US (rheumatologists, 44.8 %; allergists/immunologists, 29.3 %; dermatologists, 25.9 %) abstracted information for 147 patients (children, 46.3 %; males, 57.1 %; CAPS, 36.7 %; TRAPS, 26.5 %; FMF, 26.5 %; HIDS/MKD, 6.8 %; Mixed, 3.4 %). Overall, most patients (90.5 %) received treatment directly preceding canakinumab (NSAIDs, 27.8 % [40.0 % in HIDS/MKD]; anakinra, 24.1 % [32.7 % in CAPS]; colchicine, 21.8 % [35.9 % in FMF]), which were discontinued due to lack of efficacy/effectiveness (39.5 %) and availability of a new treatment (36.1 %). The common reasons for canakinumab initiation were physician perceived efficacy/effectiveness (81.0 %; children, 75.0 %; adults, 86.1 %), lack of response to previous treatment (40.8 %; children, 38.2 %; adults, 43.0 %) and favorable safety profile/tolerability (40.1 %; children, 42.6 %; adults, 38.0 %). Within subtypes, efficacy/effectiveness was the most stated reason for canakinumab initiation in HIDS/MKD (90.9 %), lack of response to previous treatment in FMF (52.4 %) and convenience of administration/dosing in CAPS (27.1 %). Conclusions This study provided insights into how canakinumab is initiated in US clinical practice among PFS patients, with physician perceived efficacy/effectiveness of canakinumab, lack of response to previous treatment and favorable safety profile/tolerability of canakinumab being the dominant reasons for canakinumab initiation in all patients and in children and adults and PFS subtypes. Notably, the favorable safety profile/tolerability of canakinumab was more often the reason for initiation among children versus adults.